Strategies for improving public transportation access to large airports - Coogan, Matthew A. (National Academy Press, 2002)
"This report will be of interest to individuals involved in planning and implementing improved public transportation access to large airports. Chapter 1 provides background on why this study is important at this time, which is because congestion at large airports continues to increase. Chapters 2, 3, and 4 present aspects of a market-based approach to planning ground access services to airports. Chapters 5, 6, and 7 examine management strategies for improving the quality of public transportation services to large airports. Chapter 8 integrates the entire report, summarizing key elements of the previous seven chapters and presenting a guidebook for a market-based strategy for improving public transportation access to large airports"--Description at Knovel site
Keywords: Access to airports.; Local transit.; elektronické knihy; electronic books